Efeitos in vitro da triiodotironina (T3) na diferenciação condrogênica das células-tronco mesenquimais do tecido adiposo de ratas - Elert, Nathalia Chicon (2017)
Adipose tissue-derived mesenchymal stem cells (AT-MSCs) are cells with high differentiation capacity, including chondrogenic, and there are well-defined protocols to stimulate this differentiation in vitro. Even though these cells have receptors for thyroid hormones, there are no studies investigating the effect of thyroid hormones on the chondrogenic potential of AT-MSCs. The objective of the present study was to investigate the in vitroeffect of triiodothyronine (T3) on the chondrogenic differentiation of the AT-MSCs of female rats, over several time periods and at several doses. AT-MSCs that expressed CD54, CD73, and CD90 were collected from female Wistar rats and were cultured in chondrogenic medium with or without T3. Five groups were established: 1) AT-MSCs without T3; and 2,3,4,5) AT-MSCs with 0.01, 1, 100, and 1000 nM T3, respectively). The following were evaluated at 7, 14 and 21 days: cell morphology, chondrogenic matrix formation, and expression of Sox9 and collagen II; at 21 days, collagen X expression was evaluated. For the analyses, the Student-Newman-Keuls test or the Kruskal-Wallis test was used, followed by Dunn's post hoc test. The 1000 nM dose induced an early cell-size increase at 7 days of differentiation. The hormone treatment did not alter chondrogenic matrix formation, Sox9 expression at 14 or 21 days, or expression of collagen II or collagen X at any time. However, the 0.01, 1, and 1000 nM T3 doses decreased Sox9 expression at 7 days. We conclude that T3 does not affect the chondrogenic differentiation of AT-MSCs from female rat adipose tissue because it does not alter the expression of collagen II or collagen X or the formation of chondrogenic matrix. However, it induces an early cell-size increase and decreases the expression of Sox9 in a dose-dependent manner.